(untitled) (Journal of history-rus, 2024)
During the period of Kazakhstan’s independence, the system of managing audiovisual archives underwent significant changes and went through several stages. However, over time, domestic researchers have concluded that audiovisual documents are a unique type of document that influences the renewal of historical thinking in the context of the development of modern historical science. Therefore, this type of document has also been legally ensured from a normative-legal perspective. The article examines the normative-legal framework of audiovisual documents, with a focus on the historical aspects of their formation and development. The study analyzes the evolution of legislation regulating the use of audiovisual materials, starting from the Soviet period to the present, in the context of the country’s independence. Furthermore, the article covers not only the history of the normative-legal framework for audiovisual documents in our country but also considers the current state of these documents. Various analysis methods were used in the research process, including comparative analysis, historical-legal methods, and documentary analysis. These methods helped to deepen the understanding of the process of forming the normative-legal framework and its impact on the development of the audiovisual document industry. The article explores key stages in the formation of legal systems regulating the handling, distribution, and storage of audiovisual documents, as well as the role of legal norms in ensuring cultural diversity, access to information, and protecting the interests of all participants in this process. The storage and use of audiovisual documents confirm their high legal potential. The history of forming the normative-methodological framework in the field of audiovisual documents and its current state is directly related to the practical demands of publishing historical data. Today, researchers in the country give significant attention to audiovisual documents, which significantly complement the National Archive Fund with valuable historical data. In the preservation of historical heritage, especially in periods when all confirmations are only through documents, laws, regulations, and instructions play a crucial role in society. Therefore, the article systematically addresses the relevance of legislative issues concerning audiovisual documents in modern conditions.